Prenatal predictors of infant self-regulation: the contributions of placental DNA methylation of NR3C1 and neuroendocrine activity - Conradt, Elisabeth; Fei, Mary; LaGasse, Linda; Tronick, Edward; Guerin, Dylan; Gorman, Daniel; Marsit, Carmen J.; Lester, Barry M. (Frontiers in Behavioral Neuroscience, 2015)
We examined whether placental DNA methylation of the glucocorticoid receptor gene, NR3C1 was associated with self-regulation and neuroendocrine responses to a social stressor in infancy. Placenta samples were obtained at birth and mothers and their infants (n = 128) participated in the still-face paradigm when infants were 5 months old. Infant self-regulation following the still-face episode was coded and pre-stress cortisol and cortisol reactivity was assessed in response to the still-face paradigm. A factor analysis of NR3C1 CpG sites revealed two factors: one for CpG sites 1-4 and the other for sites 5-13. DNA methylation of the factor comprising NR3C1 CpG sites 5-13 was related to greater cortisol reactivity and infant self-regulation, but cortisol reactivity was not associated with infant self-regulation. The results reveal that prenatal epigenetic processes may explain part of the development of infant self-regulation.